Answer:(2x + 9i)(2x - 9i)
Step-by-step explanation:
a^2 - b^2 = (a+b)(a-b)
a^2 + b^2 = (a+bi)(a-bi) = a^2 + abi - abi - b^2 i^2
But -b^2 i^2 = +b^2
Answer:
[tex](4x+9i)(4x-9i)[/tex]
Step-by-step explanation:
Here, we have to apply this complex numbers property:
[tex]a^2 + b^2 = (a+bi)(a-bi)[/tex]
So, the given expression [tex]4x^2+81[/tex], can be rewrite as factor using the property:
[tex]4x^2+81=(4x+9i)(4x-9i)[/tex]
Because, if
[tex]a^2=x^2 \ and \ b^2=81\\\ then \ a=x \ and \ b=9[/tex]
Therefore, the factors are [tex](4x+9i)(4x-9i)[/tex]